(untitled) (INNOVATIVE ECONOMY, 2022)
Dudynets L.A., Kvasniy M.M., Chemerys R.V. MODELLING AND CALCULATION OF THE LEVEL OF CORRUPTION INFLUENCE ON ECONOMIC ENTITIES Purpose. The aim of the article is to analyse the impact of corruption on economic entities and develop recommendations for levelling the impact of corruption on their development. Methodology of research. Economic-mathematical and statistical methods were chosen as research tools. In particular, correlation and regression analysis – to diagnose the presence and assessment of the relationship between the Corruption Perceptions Index (СРІ) and the volume of production in terms of large, medium and small enterprises. Also, economic and dynamic modelling – to formalize the dependence of production on the СРІ index in the form of growth curves and to obtain forecast estimates. Findings. The analysis of the influence of corruption on economic entities is carried out. To study corruption and its correlation with business, 3 data sets were worked out: data on the volume of production in the context of industries and size of entrepreneurship; registered cases of corruption; СРІ index. Modelling the dependence of corruption has shown that an increase in resistance to corruption increases the volume of production in a geometric order. Moreover, the model is based on exponential dependence. The forecast is based on CPI estimates – it is optimistic, the fight against corruption should grow in geometric order. Originality. The methodology for estimating the impact of corruption on economic entities based on the application of methods of economic dynamics has been improved, namely, the integration of modelling and forecasting based on correlation analysis and growth curves. As a result, the analysis and assessment of the dynamics of corruption in Ukraine and its impact on economic entities on the basis of indicators: the volume of production, the index of perception of corruption, the number of corruption cases filed in court. Practical value. The obtained results of the model and factor dependences form a significant methodological basis for modelling and calculating the level of influence of corruption on economic entities. Key words: corruption; corruption perception index; business; economic entities; level of influence; modelling.